2022
DOI: 10.3393/ac.2021.00976.0139
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics of early-onset colorectal cancer

Abstract: The aim of this study was to analysis of the clinicopathological characteristics and prognosis of colorectal cancer (CRC) under the age of 50 years. Methods: Between January 2009 and December 2018, 1,126 primary CRC patients were included from National Health Insurance Service Ilsan Hospital. The patients were divided into group 1 (n = 111, ≤ 50 years) and group 2 (n = 1,015, > 50 years). The clinicopathologic features and prognostic outcomes were compared. In addition, to analyze whether there were any differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
6
1
1
Order By: Relevance
“…[16,18,23,24,26,28-31] In a recent Korean study comparing EOCRCs with CRCs >50 years also showed higher poor histological differentiation in EOCRC group. [ 32 ] In this study, however, the aggressive pathologic features were not more common in EOCRC than in late-onset CRC. However, it may be explained that the number of CRC cases with aggressive pathologic features were small in this study and definition of aggressive pathologic features was different in each study.…”
Section: Discussioncontrasting
confidence: 56%
“…[16,18,23,24,26,28-31] In a recent Korean study comparing EOCRCs with CRCs >50 years also showed higher poor histological differentiation in EOCRC group. [ 32 ] In this study, however, the aggressive pathologic features were not more common in EOCRC than in late-onset CRC. However, it may be explained that the number of CRC cases with aggressive pathologic features were small in this study and definition of aggressive pathologic features was different in each study.…”
Section: Discussioncontrasting
confidence: 56%
“…This can reflect as well different healthcare policies between nations. A study [ 20 ] reported a worse DFS in younger patients when they were stratified according to age at diagnosis: ≤40 vs. 41–64 vs. ≥65 and 21–30 vs. 31–40 vs. 41–50. The DFS did not change when they compared two groups of patients with the cut-off age of 50.…”
Section: Discussionmentioning
confidence: 99%
“…Korea menemukan diferensiasi karsinoma kolorektal yang buruk berhubungan signifikan pada kelompok usia ≤50 tahun (Park et al, 2022). Ghodssi et al, menemukan kelompok usia yang lebih muda (<50 tahun) juga terdiagnosis dengan diferensiasi yang lebih buruk dibandingkan dengan kelompok usia tua (≥50tahun) (14,7% vs. 8,3%; p < 0.001) (Ghodssi-Ghassemabadi et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified